Properties of foamed concrete containing palm oil fuel ash - Muthusamy, Khairunisa B.; Ahmad, Saffuan Wan; Sundara, Parameswary; Kusbiantoro, Andri; Othman, R. (2018)
In Malaysia, industrial by-products namely oil palm shell, palm oil fuel ash, fly ash, and coal bottom ash continuously generated in increasing amount over the years. These materials are usually dumped as wastes which cause environmental pollution. Success in utilizing these byproducts in production of construction materials would reduce amount of waste disposed. This research was conducted to investigate the properties of lightweight concrete containing industrial wastes as mixing ingredient. Five types of lightweight concrete mixes were prepared consisting of various percentages of industrial ashes. Three types of curing were employed that is water curing, tropical air curing and 7 days initial water curing. The finding shows that selection of suitable type of curing and amount of industrial ashes used would contribute towards concrete strength enhancement. Water curing is recommended for lightweight concrete containing industrial ashes as the continuous presence of water during curing period ensure undisturbed pozzolanic reaction that vital for concrete densification. As a result, the water cured concrete specimens containing 10% ashes exhibit better strength and durability performance at all time. Water cured specimen exhibit the lowest percentage of water absorbed. Upon exposure to acid and sulphate attack, water cured specimen with 10% ashes exhibit the higher resistance with lower mass loss and strength deterioration value. Using too much of ashes as mixing ingredient in lightweight concrete is not recommended as it cause adverse effect to concrete strength and durability. Conclusively, lightweight concrete produced using industrial ash has the potential to be used in building construction.